Infective endocarditis in adults with congenital heart disease – 11 years data from Hungary. (3rd October 2022) - Bence, A; Balint, H; Borbas, S; Denes, M; Andreka, P
Abstract: Background: Despite recent preventive strategies and advances in antimicrobial and surgical treatment the incidence and mortality rate of infective endocarditis (IE) remains high in adult Congenital Heart Disease (ACHD) patients. Purpose: The aim of our retrospective study was to assess the clinical and microbiological characteristics, inhospital and one year mortality rates of ACHD patients admitted with IE in our tertiary referral hospital between 2010 and 2020. Methods: Definitive diagnosis of IE were in agreement with modified Duke's criteria. Inhospital baseline data and up to one year follow-up data were collected from the hospital records. ACHD patients were classified based on their lesion severity (ESC guideline classification). Survival data and mortality predictors were analysed by Kaplan-Meier estimator and by uni- and multivariate model. Results: 60 cases had been treated with IE. Mean age was 37±11.3 years (18–69), and most of them (76.6%, n=46) were men. ACHD complexity was as following: simple 66.7% (n=40), moderate 20% (n=12) and severe 13.3% (n=8). The most common pre-existing congenital cardiac abnormality was bicuspidal aortic valve seen in 52% (n=31) of cases. Sixty four percent (n=37) of patients had previous heart surgery (n=16, artificial heart valve surgery). Majority of patients had a left sided valve endocarditis (85%, n=51). IE related hospital stay was mean 28±9 days. Infection route was presumed in 30% of patients (n=18), they had an invasive procedure within 6 months preceding the IE diagnosis. Besides common bacterinemia caused by Staphylococcus (33%, n=20) and Streptococcus (25%, n=15), 18% (n=11) of patients had a negative blood culture. IE affected 36 patients with a native valve, and all 16 with an artificial valve. Seventy seven percent of patients required surgical intervention, immediate or urgent surgery in 22 and elective in 24 patients. Overall inhospital mortality was 13%, the majority 5 out of 8 patients having an immediate/emergent surgical intervention. IE was complicated by acute heart failure in 17 (28%) and by stroke in 4 (6.7%) patients. During one year follow-up 21 patients (38%) remained with chronic heart failure, and 3 more died. There was no significant difference in mortality between ACHD complexity groups, and no significant predictors of mortality were found. Conclusion: The most common ACHD lesion affected by IE was bicuspid aortic valve. Two-third of patients required surgical intervention, those with immediate/emergent surgery having a 22% early mortality rate. ACHD complexity was not related to early or late outcome in this population. Funding Acknowledgement: Type of funding sources: None.